True north discover your authentic leadership - George, Bill (William W.); Sims, Peter (Peter E.). (San Francisco, Calif. Jossey-Bass/John Wiley & Sons, 2007)
True North shows how anyone who follows their internal compass can become an authentic leader. This leadership tour de force is based on research and first-person interviews with 125 of today's top leaders -- with some surprising results. In this important book, acclaimed former Medtronic CEO Bill George and coauthor Peter Sims share the wisdom of these outstanding leaders and describe how you can develop as an authentic leader. True North presents a concrete and comprehensive program for leadership success and shows how to create your own Personal Leadership Development Plan centered on five key areas: a) knowing your authentic self; b) defining your values and leadership principles; c) understanding your motivations; d) building your support team; and e) staying grounded by integrating all aspects of your life. True North offers an opportunity for anyone to transform their leadership path and become the authentic leader they were born to be. -- Book jacket.
Acknowledgments -- The authors -- Editor's note / Warren Bennis -- Foreword / David Gergen -- Introduction: True North -- pt. 1. Leadership is a journey -- 1. The journey to authentic leadership -- 2. Why leaders lose their way -- 3. Transformation from "I" to "we" -- pt. 2. Discover your authentic leadership -- 4. Knowing your authentic self -- 5. Practicing your values and principles -- 6. What motivates you to be a leader? -- 7. Building your support team -- 8. Staying grounded: integrating your life -- pt. 3. Empowering people to lead -- 9. Leadership with purpose and passion -- 10. Empowering people to lead -- 11. Honing your leadership effectiveness -- Epilogue: The fulfillment of leadership -- Appendixes -- A. Research study on development of authentic leaders -- B. Authentic leaders interviewed for True North -- C. Leadership exercises for each chapter -- References -- Index.
Donated to the UP College of Public Health by the Zuellig Family Foundation thru the Health Leadership and Governance program
Keywords: Leadership; Organizational effectiveness